Impact of podcasts in teachers education : from consumers to producers - Carvalho, Ana Amélia Amorim (2009)
Podcasts are being used in higher education, particularly in blended-learning or in distance learning. Studies in different universities have reported its use with different purposes. The research described in this paper reports to a study conducted in Portugal in three courses, one of a teaching program of Biology and the other two of Educational Master programs. The students (n= 82) liked the podcasts and showed to be receptive to have podcasts in other courses. The undergraduate students only listened to podcasts. The Master students created their own podcasts to get familiar with them and to understand how easy it is to create them. They mentioned that they realized the importance of its use in learning.